2021
DOI: 10.1007/s11244-021-01468-3
|View full text |Cite
|
Sign up to set email alerts
|

Toward E-selective Olefin Metathesis: Computational Design and Experimental Realization of Ruthenium Thio-Indolate Catalysts

Abstract: The selective transformation of 1-alkenes into E-olefins is a long-standing challenge in olefin metathesis. Density functional theory (DFT) calculations predict high E-selectivity for catalysts incorporating a bidentate, dianionic thio-indolate ligand within a RuXX’(NHC)(py)(= CHR) platform (NHC = N-heterocyclic carbene; py = pyridine). Such complexes are predicted to yield E-olefins by favoring anti-disposed substituents in the transition state expected to be rate-determining: specifically, that for cycloreve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(22 citation statements)
references
References 79 publications
5
17
0
Order By: Relevance
“…It is observed that this approach focused on stereoselectivity differs from other sulfur chelates previously reported, in which the ether R 2 O→Ru in HG catalysts is replaced by a thioether R 2 S→Ru, resulting in enhancements in the catalytic activity. It should be clarified, however, that we aimed at the formation of an active species that resembles the structure depicted in Scheme b. In this regard, several authors have previously reported predictive catalysis based on DFT calculations verified by experimental evidence. …”
Section: Introductionmentioning
confidence: 98%
“…It is observed that this approach focused on stereoselectivity differs from other sulfur chelates previously reported, in which the ether R 2 O→Ru in HG catalysts is replaced by a thioether R 2 S→Ru, resulting in enhancements in the catalytic activity. It should be clarified, however, that we aimed at the formation of an active species that resembles the structure depicted in Scheme b. In this regard, several authors have previously reported predictive catalysis based on DFT calculations verified by experimental evidence. …”
Section: Introductionmentioning
confidence: 98%
“…Since its accidental discovery by Phillips Petroleum Co., olefin metathesis has been instrumental as a simple and robust synthetic method for the redistribution of carbon–carbon double bonds . In particular, ring-opening metathesis polymerization (ROMP) is an excellent method for the synthesis of polymers with well-defined molecular weights and monomer sequences, high thermomechanical and chemical property ceilings, and controlled stereochemistries. , Polydicyclopentadiene (pDCPD), a thermosetting polymer produced by ROMP of dicyclopentadiene (DCPD), has been of notable interest to academia as the relatively high ring-strains of the norbornene and cyclopentene moieties in DCPD provide sufficient reactivity for its use as a model compound in catalyst development (Figure a). , Additionally, pDCPD has found broad industrial use due to its high impact strength, desirable chemical and thermal stability, and corrosion resistance properties. ,, Applications of pDCPD include heavy-vehicle paneling, sporting equipment, and electrolytic cell coverings. Thus far, the applications of pDCPD are limited to large parts with relatively simple geometries produced by reaction injection molding due to the use of highly active transition metal catalysts (e.g., ruthenium) that rapidly polymerize DCPD upon mixing of monomer and catalyst. Recent developments in latent catalysis and additive manufacturing (AM) of olefin metathesis resins offer exciting alternative methods for the manufacturing of pDCPD to achieve complex, highly resolved architectures not possible with traditional processing techniques. …”
Section: Introductionmentioning
confidence: 99%
“…24 The computational insights can facilitate a rational design and selection of new candidates, thereby saving significant resources and time, 25 as shown for instance in works dedicated to the design and development of (Z)-selective catalysts for the cross-metathesis reaction. 22,26,27 With the overall goal of addressing the remaining challenges in the transfer C−H borylation of alkenes, we aim to gain further insights into the reaction and understand the catalyst structure− activity and selectivity relationships. Here, we present our studies to reveal how the electronic and steric features of the phosphine ligand of the Rh catalyst influences the activity and selectivity of the transfer C−H borylation reaction.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Such studies are particularly attractive prior to tedious experimentation required for the synthesis of new putative catalysts . The computational insights can facilitate a rational design and selection of new candidates, thereby saving significant resources and time, as shown for instance in works dedicated to the design and development of ( Z )-selective catalysts for the cross-metathesis reaction. ,, …”
Section: Introductionmentioning
confidence: 99%